Distinct Immunological Profiles Help in the Maintenance of Salivary Secretory IgA Production in Mild Symptoms COVID-19 Patients - Santos, Juliana de Melo Batista dos; Amaral, Jonatas Bussador do; França, Carolina Nunes; Monteiro, Fernanda Rodrigues; Alvares-Saraiva, Anuska Marcelino; Kalil, Sandra; Durigon, Edison Luiz; Oliveira, Danielle Bruna Leal; Rodrigues, Silvia Sanches; Heller, Debora; Welter, Eliane Aparecida Rosseto; Pinho, João Renato Rebello; et al. (Frontiers in Immunology, 2022)
Background: Relevant aspects regarding the SARS-CoV-2 pathogenesis and the systemic immune response to this infection have been reported. However, the mucosal immune response of the upper airways two months after SARS-CoV-2 infection in patients with mild/moderate symptoms is still not completely described. Therefore, we investigated the immune/inflammatory responses of the mucosa of the upper airway’s of mild/moderate symptoms COVID-19 patients two months after SARS-CoV-2 infection in comparison to a control group composed of non-COVID-19 healthy individuals. Methods: A cohort of 80 volunteers (age 37.2 ± 8.2), including non-COVID-19 healthy individuals (n=24) and COVID-19 patients (n=56) who presented mild/moderate symptoms, during a COVID-19 outbreak in Brazil in November and December of 2020. Saliva samples were obtained two months after the COVID-19 diagnosis to assess the levels of SIgA by ELISA and the cytokines by multiplex analysis. Results: Salivary levels of SIgA were detected in 39 volunteers into the COVID-19 group and, unexpectedly, in 14 volunteers in the control group. Based on this observation, we distributed the volunteers of the control group into without SIgA or with SIgA sub-groups, and COVID-19 group into without SIgA or with SIgA sub-groups. Individuals with SIgA showed higher levels of IL-10, IL-17A, IFN-γ, IL-12p70, IL-13, and IFN-α than those without SIgA. In intergroup analysis, the COVID-19 groups showed higher salivary levels of IL-10, IL-13, IL-17A, and IFN-α than the control group. No statistical differences were verified in the salivary levels of IL-6 and IFN-β. Lower IL-12p70/IL-10 and IFN-γ/IL-10 ratios were found in the control group without SIgA than the control group with SIgA and the COVID-19 group with SIgA. Conclusion: We were able to present, for the first time, that associations between distinct immunological profiles can help the mucosal immunity to maintain the salivary levels of SIgA in COVID-19 patients two months after the SARS-CoV-2 infection.